Analysing the preferences for family doctor contract services in rural China: a study using a discrete choice experiment - Peipei Fu; Yi Wang; Shimeng Liu; Jiajia Li; Qiufeng Gao; Chengchao Zhou; Qingyue Meng; Sean Sylvia (BMC Family Practice, 2020)
Abstract Background Preliminary evaluations have found that family doctor contract services (FDCSs) have significantly controlled medical expenses, better managed chronic diseases, and increased patient satisfaction and service compliance. In 2016, China proposed the establishment of a family doctor system to carry out contract services, but studies have found the uptake and utilization of these services to be limited. This study aimed to investigate rural residents’ preferences for FDCSs from the perspective of the Chinese public. Methods A discrete choice experiment (DCE) was performed to elicit the preferences for FDCSs among rural residents in China. Attributes and levels were established based on a literature review and qualitative methods. Five attributes, i.e., cost, medicine availability, the reimbursement rate, family doctor competence, and family doctor attitude, were evaluated using a mixed logit model. Results A total of 609 residents were included in the main DCE analysis. The respondents valued the high competence (coefficient 2.44, [SE 0.13]) and the good attitude (coefficient 1.42, [SE 0.09]) of family doctors the most. Cost was negatively valued (coefficient − 0.01, [SE 0.01]), as expected. Preference heterogeneity analysis was conducted after adjusting the interaction terms, and we found that rural residents with higher educational attainment prefer a good attitude more than their counterparts with lower educational attainment. The estimated willingness to pay (WTP) for “high” relative to “low” competence was 441.13 RMB/year, and the WTP for a provider with a “good” attitude relative to a “poor” attitude was 255.77 RMB/year. Conclusion The present study suggests that strengthening and improving the quality of primary health care, including the competence and attitudes of family doctors, should be prioritized to increase the uptake of FDCSs. The contract service package, including the annual cost, the insurance reimbursement rate and individualized services, should be redesigned to be congruent with residents having different health statuses and their stated preferences.